Uso de nudges no combate à fraude em programas de integridade - Carvalho, Barbara Padilha de (2019)
Objective of the Paper: This paper aimed to identify which nudges can be used by organizations to institutionalize fraud risk prevention in compliance programs, implemented in accordance to the Law 12.846 / 2013. In terms of theories, the research was based on the concepts of fraud, institutional theory, compliance program and nudges. Design / methodology / approach: Methodologically, this study is classified as qualitative, using a non-experimental, transversal, exploratory and descriptive research model. Data collection was done through interviews, in which a questionnaire of open questions was applied, to eight professionals who are responsible for the implementation of compliance programs (compliance officers), professionals responsible for internal auditing, professionals who act as external auditors and professionals who work in the area of consulting for compliance purposes (investigation, testing on controls). All interviews were recorded and transcribed and the data were examined using Content Analysis. Results: As a result of this paper, it is worth mentioning the transformation of the organizational culture to the legitimacy of compliance programs in organizations. This legitimization process must start at the top (tone at the top) to inspire people to adopt internal controls effectively and efficiently. The opportunities for fraud occur through failures in the system and through the existence of people who have the motivation and rationalize a fraud, therefore, as a result of this work, a list of the important characteristics that the professionals who act in the management of compliance programs should present in their profiles was provided. In addition, the results of this research have presented the key controls to mitigate the risk of fraud correlated with the legitimation mechanisms of compliance programs. Finally, the results point to the benefits of implementing integrity programs, correlating the nudges that must be used in these programs to avoid frauds. Nudges, once they are behavioral mechanisms, should support relevantly in this process of cultural transformation and legitimation of compliance programs. Practical implications: This work has practical implications for Brazilian organizations that have implemented or plan to implement compliance programs, a topic in national studies, especially since the enactment of Law 12.846 / 2013 and Decree No. 8,420 / 15, as well as the notoriety given to the topic after the outbreak of operations of corruption investigations, starting in 2014, such as Operation Lava Jato. Originality and contributions: This study aimed to contribute to the process of legitimizing compliance programs to be adopted or already adopted by organizations, through the use of nudges, bringing a concept of behavioral economics to the field of the internal control environment, whose objective, among others, is to prevent and detect fraud in organizations. The issues explored in this study support the institutionalization of compliance programs in a mimetic way, that is, based on best market practices to the detriment of coercive and / or normative forms. In addressing the mimetic form of institutionalization, we also addressed the engagement of the executives responsible for both Governance and the activities of organizations in line with the compliance programs, in order to support the legitimation of a new organizational culture that sees the benefits of implementing these programs qualitatively.